Table of Content - -, (Journal of agricultural, environmental and veterinary sciences, 2025)
Table of Content:1. Agricultural production in the southern central Rif: between traditional practices and the desire  for modernization and intensification "Taounate District as a model"Dr. Hini Mohammed, Dr. El-Bazoui Jaouad, Dr. Errafik Mohammed2. Assessment of the Population Structure and Regeneration Status of Different Communities  of Vachellia gerrardii in Al-Haski Valley, Al-Taysia Reserve, Kingdom of Saudi ArabiaMr. Maher Mohammad Bali,Prof. Ahmed Abdullah Al-Dughairi ,Dr. Ali Ebrahem Al-Zubaidi3. The impact of urban expansion on the vegetation cover in the city of Baqaa using geographic information systems during the period (1990-2024 AD)Dr. Seham Sayer Khalif Al-Shammari
Keywords: Journal of Agricultural, Environmental and Veterinary Sciences